Temporal Theta Power is Related to Age and Working Memory Functioning: Putative Biomarkers for Detecting Non-Salient Pathological Brain States in Older People - Oded Meiron (BJPsych Open)
Aims: In adult humans, WM-related EEG theta dynamics are hypothesized to reflect involvement of prefrontal-hippocampal theta-rhythms in the integration of working-memory associations into unitary coherent memory representations accessible for selection during memory retrieval. Therefore, medial temporal lobe (MTL) theta oscillations are hypothesized to drive the retention of novel verbal WM associations in humans. Several studies in adult samples reported an increase in theta activity during the WM retention delay. However, the impact of ageing on fronto-temporal power during verbal WM tasks (associated with MTL network plasticity), and on WM performance differences between younger age groups versus older people needs to be further examined. Thus, we aimed to show a significant relationship between theta activity and WM across the lifespan, and to suggest novel diagnostic markers sensitive to early WM memory impairment associated with ageing and prodromal stages of Alzheimer’s disease (AD). Thus, increased theta power, which is required to maintain verbal information under different WM loads is predicted to be lower in older adults versus younger adults, specifically, under lateral fronto-temporal-parietal electrode locations, and during verbal WM retention intervals.